IMPLEMENTASI PUTUSAN JUDICIAL REVIEW MAHKAMAH KONSTITUSI NOMOR. 4/PUU-XVII/2019 DALAM PENGUJIAN PASAL 2 AYAT (2) UNDANG-UNDANG NOMOR. 20 TAHUN 2001 PERUBAHAN ATAS UNDANG-UNDANG NOMOR. 31 TAHUN 1999 TENTANG PEMBERANTASAN TINDAK PIDANA KORUPSI TERKAIT PIDANA MATI DALAM KEADAAN BENCANA ALAM - Khaira Islamaili; Erdianto Effendi; Adi Tiara Putri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
For example, the corruption case against aid funds affected by naturaldisasters in 2018 in Donggala against the defendants Muhir and H.Silmi whopoured money for the rehabilitation of mosques and schools that did not receivesanctions as stated in the article that was violated, so that there was a review ofthe article that was violated in the Constitutional Court Decision Number 4/PUU-XVII/2019. In addition, there is also a corruption case against social assistancefunds for handling the Covid-19 pandemic or known as the Bansos corruption thatis currently occurring, against the defendants Juliari Batubara and Matheus JokoSantoso. For this reason, extraordinary efforts are needed in eradicating thecrime of corruption, by imposing the toughest sanctions on the perpetrators ofcorruption in order to provide fear and a deterrent effect, both to the perpetratorsand to other people who have the potential to commit corruption crimes, namely:death penalty as stipulated in the formulation of Article 2 paragraph (2) of LawNo. 31 of 1999 in conjunction with Law Number 20 of 2001 concerning theEradication of Criminal Acts of Corruption.This type of research can be classified as normative legal research byapproaching legislation or literature study with books, articles, newspapers asresearch materials and sources.From the results of the research conducted, it can be concluded that there isno legal certainty in interpreting "certain circumstances" as criminal penalties forperpetrators of criminal acts of corruption. Therefore, it is necessary to reformthe substance or material in the formulation of the death penalty in Article 2paragraph (2) of the Law on the Eradication of Criminal Acts of Corruption sothat it is in accordance with the values of justice and legal certainty.Keywords: Death Penalty – Corruption - Natural Disaster